HIV/AIDS, food security and rural livelihoods: Understanding and responding - Loevinsohn, Michael E.; Gillespie, Stuart (International Food Policy Research Institute, 2003)
There is hardly need these days to repeat that HIV/AIDS is devastating African societies and economies, threatening the hard-won human development gains of the past several decades. The changes to the development landscape wrought by AIDS demand a review of existing development actions at many levels, from households seeking to secure viable livelihoods, to policymakers attempting to better understand and internalize the implications of AIDS for their own sectoral goals and strategies. In this paper, we describe processes of understanding and responding that are needed for HIV/AIDS to be effectively addressed. Key concepts of resistance and resilience are illustrated through a discussion of the two-way interactions between food insecurity and HIV/AIDS, and their implications for the ways in which affected households, communities, and sectors may best respond. One major set of responses is required from the agriculture sector, as the need to secure and provision food for populations affected by HIV/AIDS is rapidly increasing as the impact waves hit. Food is the first priority of many people affected by the pandemic. We are also beginning to learn more about the crucial role of nutritional status--both in terms of susceptibility to HIV infection and transmission and in terms of the quality and quantity of life of HIV-positive individuals. A sea change is required--in attitudes and consciousness of what HIV/AIDS is doing at different levels and the pathways through which it moves through societies. Such a new awareness may be facilitated by the use of an 'HIV/AIDS lens' -- essentially a tool for reviewing situations and development actions from the perspective of our evolving knowledge of AIDS interactions. The lens will facilitate the development of more HIV-relevant policies and programs of more sectors--and ultimately in larger scale, sustained progress in responding to AIDS. While the specifics will become clear through use of the lens, external support will likely be most effective in the long run where it is directed to preserving and developing institutional capacities to strengthen resistance and resilience.